Differentiated factors drive the spatial heterogeneity of ecosystem services in Xinjiang Autonomous Region, China - Zhang, Zhiru; Wan, Huawei; Peng, Shilei; Huang, Lin (Frontiers in Ecology and Evolution, 2023)
Exploring the driving factors of changing ecosystem services is critical for supply capacity maintaining and ecological management zoning. Xinjiang of Northwest China, is considered one of the most fragile ecological environment areas. However, studies on how ecosystem services’ driving forces respond to the environmental conditions of Xinjiang are still insufficient, especially in sub–regions with considerable spatial heterogeneity. Based on 106 counties across Xinjiang, we employed models of the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) and Revised Wind Erosion Equation (RWEQ) to quantify four essential ecosystem services (carbon storage, habitat quality, sand fixation and water yield). Then, we investigated the spatial distribution of four ecosystem services and drivers at the county scale in 2020 by using multi–scale geographically weighted regression (MGWR). Analysis of spatial changes in various ecosystem service patterns and driving factors has shown that: (1) The spatial distribution of ecosystem services is higher in the North and lower in the South, and hotspots and high–value ecosystem services areas were consistent. There is spatial heterogeneity of ecosystem services among counties. (2) Precipitation, temperature, and fractional vegetation cover were the dominant factors influencing the four ecosystem services. The percentage of an urban area and population density have the most negligible impact on ecosystem services. To sum up, ecological factors had a significantly higher impact than social factors. (3) Significant differences exist in the counties of the type, intensity, and direction of ecosystem services drivers. The influence of the driving force on ecosystem services varies with spatial distribution. The correlation between carbon storage, habitat quality and fractional vegetation cover is more robust stronger in the South. Water yield is more closely related to fractional vegetation cover in Southern Xinjiang. Under different ecological and social conditions, the impact of driving forces on ecosystem services shows different changing trends. A comparative analysis of the driving factors of ecosystem services at a county scale will help to develop differentiated ecological protection policies and promote a sustainable supply of ecosystem services in Xinjiang.